2018
DOI: 10.22616/erdev2018.17.n398
|View full text |Cite
|
Sign up to set email alerts
|

Effect of biological preparation on changes in soil organic carbon and its environmental impact applying precision farming

Abstract: Abstract. Soil organic carbon is one of the key qualitative soil parameters. I`t affects soil vitality, its humus content, microorganism activity, soil CO 2 emissions, as well as basic fertilizer needs and plants' ability to source nutrients. According to Christopher and Lal (2007), the carbon (C) cycle is closely related to the nitrogen (N) cycle in plants and soil organic matter. The application of precision farming can aid in determining the exact content of organic carbon in soil and the appropriate carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Scientific results showed that the preparation of biocrusts biopreparation significantly improved soil physicochemical properties, respiration, and alkaline phosphatase, protease, and cellulose, and reduced CO2 emissions in vegetation areas (Liu et al, 2017). A team of researchers (Juknevičius et al, 2018) found that biopreparations increased soil organic carbon by up to 0.2%, which can have an impact on soil respiration.…”
Section: Co2 Emissions From Soilmentioning
confidence: 99%
“…Scientific results showed that the preparation of biocrusts biopreparation significantly improved soil physicochemical properties, respiration, and alkaline phosphatase, protease, and cellulose, and reduced CO2 emissions in vegetation areas (Liu et al, 2017). A team of researchers (Juknevičius et al, 2018) found that biopreparations increased soil organic carbon by up to 0.2%, which can have an impact on soil respiration.…”
Section: Co2 Emissions From Soilmentioning
confidence: 99%